2020
DOI: 10.1016/j.bjid.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Triage tool for suspected COVID-19 patients in the emergency room: AIFELL score

Abstract: Clinical prediction scores support the assessment of patients in the emergency setting to determine the need for further diagnostic and therapeutic steps. During the current COVID-19 pandemic, physicians in emergency rooms (ER) of many hospitals have a considerably higher patient load and need to decide within a short time frame whom to hospitalize. Based on our clinical experiences in dealing with COVID-19 patients at the University Hospital in Zurich, we created a triage score with the acronym "AIFELL" consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…The population understands some words, like "therapeutic obstinacy, " and in fact the idea is to use these words, but not everyone is really able to understand them." (Participant 4, age range [31][32][33][34][35][36][37][38][39][40] One participant added that the difficulty to address endof-life issues is also common among HCPs and not only family members: "Colleagues lack sensitivity on this. .…”
Section: Paternalism's Comebackmentioning
confidence: 99%
See 1 more Smart Citation
“…The population understands some words, like "therapeutic obstinacy, " and in fact the idea is to use these words, but not everyone is really able to understand them." (Participant 4, age range [31][32][33][34][35][36][37][38][39][40] One participant added that the difficulty to address endof-life issues is also common among HCPs and not only family members: "Colleagues lack sensitivity on this. .…”
Section: Paternalism's Comebackmentioning
confidence: 99%
“…Think about how difficult this is to accept." (Participant 4, age range [31][32][33][34][35][36][37][38][39][40] Participants also reported that the absence of the family members, who could not be close to the patients in the hospital and frequently interact with the care team, accentuated this form of paternalism and prevented a shared decision making approach.…”
Section: Paternalism's Comebackmentioning
confidence: 99%
“…Severity of disease was classified according to Siddiqi [5]. The risk stratification by the AIFELL score was documented [6]. Data on antiviral, antibiotic and anti-inflammatory therapy were recorded, as well as clinical treatment setting (normal ward, intermediate care, and intensive care).…”
Section: Study Population Setting and Clinical Datamentioning
confidence: 99%
“…The AIFELL score, developed by Levenfus et al, is a clinical prediction score used for triage purposes to assess risk and provide guidance of further diagnostic and therapeutic steps in patients suspected to have COVID-19 [6]. It can be easily applied in emergency wards, and also has an interactive website (www.aifell.net) correlating the AIFELL score to the above-mentioned Siddiqi stages.…”
Section: Aifell Scorementioning
confidence: 99%
“…With the highly developed health-care system, technology, and communication infrastructures in Dubai, it was manageable to deal with the large flow of patients on daily basis. One way to overcome this challenge was (Triage Score) as done by the University Hospital in Zurich, who created a triage score to help the doctors at ER to decide if the patient needs hospital admission or could be discharged to home isolation which consists of clinical, radiological, and laboratory findings [ 2 ].…”
Section: Introductionmentioning
confidence: 99%